2020
DOI: 10.1055/a-1129-7214
|View full text |Cite
|
Sign up to set email alerts
|

Tormentillae rhizoma – Review for an Underestimated European Herbal Drug

Abstract: Potentilla erecta is a medicinal plant described under its traditional name Tormentil in medieval herbal books and used until today in many European countries. Today monographs for Tormentillae rhizoma in the European pharmacopeia, as well as a monograph of the Herbal Medicinal Product Commission as a drug for traditional use, exist. The present review summarizes published investigations in phytochemistry and pharmacology, together with new findings reflecting the mechanisms of action of ellagitannins as one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Chemical composition. Hydrolysable tannins (pedunculagin, pentadigalloylglucose, agrimoniin, laevigatin B, tormentillin); condensed tannins/proanthocyanidins ([4,6]-all-trans-bi-(+)-catechin = procyanidin B6, [4,8]-2,3-trans-3,4-cis-bi-(+)-catechin, [4,8]-all-trans-bi-(+)-catechin = procyanidin B3), [6′,6]-all-trans-bi-(+)-catechin, procyanidin B1, procyanidin B2, procyanidin B5, (+)-catechin-[4,8]-(+)-catechin-[4,8]-(+)-catechin, (+)-catechin-[6′,8]-(+)-catechin-[4,8]-(+)-catechin; triterpenoids: 2α,3β-dihydroxyurs-12 -en-28-oic acid β-D-glucopyranosyl ester, 3-epi-pomolic acid 28- O -β-D-glucoside, 3β,19α-dihydroxyolean-12-en-28-oic acid β-D-glucopyranosyl ester, 3β,19α-dihydroxyurs-12-en-28-oic acid β-D-glucopyranosyl ester, arjunetin, chinovic acid, kaji-ichogoside F1, tormentic acid, tormentoside ( Tomczyk and Latté, 2009 ; Melzig and Böttger, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical composition. Hydrolysable tannins (pedunculagin, pentadigalloylglucose, agrimoniin, laevigatin B, tormentillin); condensed tannins/proanthocyanidins ([4,6]-all-trans-bi-(+)-catechin = procyanidin B6, [4,8]-2,3-trans-3,4-cis-bi-(+)-catechin, [4,8]-all-trans-bi-(+)-catechin = procyanidin B3), [6′,6]-all-trans-bi-(+)-catechin, procyanidin B1, procyanidin B2, procyanidin B5, (+)-catechin-[4,8]-(+)-catechin-[4,8]-(+)-catechin, (+)-catechin-[6′,8]-(+)-catechin-[4,8]-(+)-catechin; triterpenoids: 2α,3β-dihydroxyurs-12 -en-28-oic acid β-D-glucopyranosyl ester, 3-epi-pomolic acid 28- O -β-D-glucoside, 3β,19α-dihydroxyolean-12-en-28-oic acid β-D-glucopyranosyl ester, 3β,19α-dihydroxyurs-12-en-28-oic acid β-D-glucopyranosyl ester, arjunetin, chinovic acid, kaji-ichogoside F1, tormentic acid, tormentoside ( Tomczyk and Latté, 2009 ; Melzig and Böttger, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the clinical evidence is Low, this herbal medicine is considered presenting High safety. (Tomczyk and Latte, 2009;Melzig and Böttger, 2020).…”
Section: Polypodium Vulgare L -Polypodiaceae (Rhizomes)mentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Potentilla L (Rosaceae family) consists of approximately 700 species of annual and biennial plants and small shrubs. Extract from the underground parts of Potentilla erecta (L.) Raeusch (tormentil extract [TE]) has been used in traditional ethnomedicine for the treatment of diarrhea and mild inflammation of the oral mucosa because of its antioxidant and anti-inflammatory activity (Tomczyk and Latté, 2009;Melzig and Böttger, 2020;Augustynowicz et al, 2021). The pharmacological properties of tormentil have been discussed in several reviews and it's monographs are included in the Russian Pharmacopoeia (14th edition), State Pharmacopoeia of the Republic of Belarus, ESCOP, in the British Pharmacopoeia, or the European Pharmacopoeia (10th edition) (Shikov et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on in vitro models have shown the astringent, antimicrobial, antioxidant, and anti-inflammatory effects of tormentil rhizomes [ 101 ].…”
Section: Phytotherapy In Skin Diseasesmentioning
confidence: 99%